2009
DOI: 10.1210/en.2009-0499
|View full text |Cite
|
Sign up to set email alerts
|

Fetal and Neonatal Exposure to the Endocrine Disruptor Methoxychlor Causes Epigenetic Alterations in Adult Ovarian Genes

Abstract: Exposure to endocrine-disrupting chemicals during development could alter the epigenetic programming of the genome and result in adult-onset disease. Methoxychlor (MXC) and its metabolites possess estrogenic, antiestrogenic, and antiandrogenic activities. Previous studies showed that fetal/neonatal exposure to MXC caused adult ovarian dysfunction due to altered expression of key ovarian genes including estrogen receptor (ER)-beta, which was down-regulated, whereas ERalpha was unaffected. The objective of the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
98
0
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(109 citation statements)
references
References 101 publications
7
98
0
1
Order By: Relevance
“…Studies using transfected cell lines have demonstrated that the active metabolites of MXC are agonists of ESR1, but antagonists for both ESR2 and AR (Gaido et al 2000). Other studies have shown that fetal and neonatal exposure to MXC (20 mg/kg and 100 mg/kg) alters methylation on the promoter region of ESR2 and therefore suppresses the expression of ESR2, causing ovarian dysfunction in the rat (Armenti et al 2008, Zama & Uzumcu 2009). Interestingly, antral follicles overexpressing ESR1 have been shown to be more sensitive to toxicity by MXC and its metabolites in both in vivo and in vitro experiments (Tomic et al 2006.…”
Section: Chemicals That Alter Hormone Receptor Binding and Actionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies using transfected cell lines have demonstrated that the active metabolites of MXC are agonists of ESR1, but antagonists for both ESR2 and AR (Gaido et al 2000). Other studies have shown that fetal and neonatal exposure to MXC (20 mg/kg and 100 mg/kg) alters methylation on the promoter region of ESR2 and therefore suppresses the expression of ESR2, causing ovarian dysfunction in the rat (Armenti et al 2008, Zama & Uzumcu 2009). Interestingly, antral follicles overexpressing ESR1 have been shown to be more sensitive to toxicity by MXC and its metabolites in both in vivo and in vitro experiments (Tomic et al 2006.…”
Section: Chemicals That Alter Hormone Receptor Binding and Actionmentioning
confidence: 99%
“…Early studies with BPA showed that it has estrogenic properties and its binding affinity to ESRs is lower than E 2 or DES (Zama & Uzumcu 2009). In vitro, BPA acts as an agonist for both ESR1 and ESR2 on a tissue-specific basis (Kurosawa et al 2002), although in vivo findings suggest that it can also antagonize ESR2 function (Susiarjo et al 2007).…”
Section: Chemicals That Alter Hormone Receptor Binding and Actionmentioning
confidence: 99%
“…Methoxychlor (MXC), an organochloride pesticide with oestrogenic activity mediated primarily via ERb (Zama & Uzumcu 2009), caused ovarian dysfunction in the adult rodent following exposure to rats during the foetal or neonatal period. Follicle composition was altered with more preantral and early antral follicles present and fewer CL (Gray et al 1989).…”
Section: Environmental Oestrogensmentioning
confidence: 99%
“…by modulating gene expression without modifying the underlying DNA sequence. The perinatal exposure to MXC has, indeed, been shown to cause an hypermethylation of the ESR2 promoter and of ten other genes in the ovary (Zama & Uzumcu 2009).…”
Section: Introductionmentioning
confidence: 99%